PEMBELAJARAN BAHASA-SASTRA MULTILITERASI: EVALUASI DAN REMIDIASI - Ilham Fadli, Rusli (Discovery, 2016)
This study focused on the process of learning using type of cooperative learning model, barriersto learning, student achievement during the learning and teaching model of cooperative-typelinkage with increased ability of students in the analysis of the clause. This study aims todetermine the learning process, barriers to learning, student achievement during the learning andteaching model of cooperative-type linkage with increased ability of students in the analysis ofthe clause.One of the problems that arise in the course of learning the syntax is generally donewith college pulpit so that the learning is centered on the lecturer. This causes saturation forstudents and not the appearance of the activity within the student. Therefore it is necessary tohave appropriate learning models in the course of Syntax, one with a model of the type ofcooperative learning.